A temperature-responsive poly(vinyl alcohol) gel for controlling fluidity of an inorganic phase change material. Issue 24 (1st June 2017) - Karimineghlani, Parvin; Emmons, Emily; Green, Micah J.; Shamberger, Patrick; Sukhishvili, Svetlana A.
Abstract : A temperature-responsive PVA gel is achieved that reversibly holds fluid lithium nitrate trihydrate and releases it in response to temperature for easy gelling in-place and later removal from heat-exchange modules. Abstract : An environmentally responsive polymeric network has been demonstrated for incorporating an inorganic salt hydrate phase change material (PCM). The unique feature of this material is the capability of a polymer gel to simultaneously provide shape stabilization of a liquid salt hydrate phase at a lower temperature, and to reversibly adjust its assembly strength in response to a temperature increase. This approach enables convenient control over the viscosity of the PCM gel system, allowing for filling and removal of the mixture in a liquid state but operation in the solid/gel regime. The system consists of poly(vinyl alcohol) (PVA) dissolved in lithium nitrate trihydrate (LNH), a high-latent-heat salt hydrate PCM. Dynamic light scattering (DLS) and viscometry studies indicate that in dilute solution, PVA chains are more expanded in LNH than in water. At a concentration of 15 wt% PVA, the PVA/LNH system – unlike PVA aqueous solutions – gels and exhibits a temperature-triggered gel-to-sol transition. Gelation is achieved only with PVA with the highest degree of hydrolysis (98%), with the gelation temperature of 20 ± 1 °C as measured by DLS and rheology. ATR-FTIR spectroscopy shows that the PVA gelation is enhanced due to dehydration of PVA chains in LNH, as compared to PVA aqueous solutions. Physically crosslinked PVA/LNH gels demonstrate highly repeatable and reproducible performance during ten cycles of LNH melting/freezing, as shown by differential scanning calorimetry (DSC). Taken together, these results confirm that PVA-based gels are promising matrices for hosting inorganic PCMs that withstand repeated melting/freezing cycling, but can be easily filled or drained as needed by raising the temperature well above the gelation temperature.